Transient Vibration of Unsteady Linear Closed Loop Systems - Wittbrodt, E.; Kaliński, K.J. (Engineering Transactions, 1999)
A problem of unsteady linear closed loop system vibration is formulated and solved in this paper. Proportional, ideal derivative and delayed feedback interaction is considered. The mixed method of rigid and deformable finite elements is extended by including coupling elements, and applied to modelling the system. An unconditionally stable numerical integration variant of the Newmark method is used for solving the problem. Special computer software is implemented and illustrative calculations of the traverse shaper's model are performed. Time and frequency plots for chosen generalised coordinates of the model and for several cases of the feedback interaction, are obtained as results.